Flow injection analysis of total curcuminoids in turmeric and total antioxidant capacity using 2,2′-diphenyl-1-picrylhydrazyl assay - Wisanu Thongchai (2018)
A simple flow injection analysis procedure is proposed for the determination of curcuminoids content in turmeric extracts. The method is based on the formation of a coloured complex between 4-aminoantipyrine and curcuminoids, in the presence of an oxidising reagent such as potassium hexacyanoferrate (III) in alkaline media. Conditions selected as a result of these trials were implemented in a flow injection analytical system in which the influence of injection volume, flow rate, reagent concentration and mixing coil length, was evaluated. Under the optimum conditions the total amount of curcuminoids could be determined within a concentration range of 5-50 μg mL-1which can be expressed by the regression equation y = 0.003x - 0.0053 (r2= 0.9997). The limits of detection and quantitation were found to be 0.6 μg mL-1and 1.8 μg mL-1, respectively. The reproducibility of analytical readings was indicative of standard deviations <2%. The sample was extracted and analysed by using the proposed method. The percentage recoveries were found to be 94.3-108.0. The proposed system was applied to the determination of curcuminoids content in turmeric. The total curcuminoid contents in turmeric extract were found to be 0.9-4.3% (w/w). The development method is simple, economic, rapid and especially suitable for quality control in pharmaceutical plants. © 2008 Elsevier Ltd. All rights reserved.